Gan-du-qing attenuates PM2.5-induced Chronic Airway Inflammation via regulating the pulmonary microbiota and metabolic profiles - Wu, Yongcan; Zuo, Biao; Zhou, Xin; Zhao, Sijing; Pei, Caixia; Wang, Xiaomin; Wang, Yilan; Huang, Demei; Shi, Shihua; Shen, Zherui; Wang, Jianwei; Wang, Fei; et al. (Frontiers in Medicine, 2025)
BackgroundSubstantial evidence links fine particulate matter (PM2.5) to the development of inflammatory lung diseases such as chronic airways, but effective treatments are lacking. Gan-du-qing (GDQ) Decoction is a traditional Chinese medicine formula for chronic airway inflammation. However, whether GDQ can ameliorate PM2.5-induced lung injury and its mechanism are unknown, and we will further investigate.Study design/MethodsMale Sprague-Dawley (SD) rats weighing 120 grams were utilized to establish a rat model of lung injury through systemic exposure to PM2.5. We built a real environmental exposure chamber with an exposure period of 16 weeks and the average concentration exposed was 110.5 μg/mł. The exposure chamber is located at 12 Bridge Road, Chengdu City, and the exposure time is from November to February of the second year. GDQ was administered via gavage starting 4 weeks post-exposure. Morphological changes were observed through Hematoxylin and Eosin (HE) staining. Inflammatory cell infiltration was detected using immunohistochemical staining, while scanning electron microscopy was employed to observe ultrastructural changes in the lung trachea. Levels of inflammatory cytokines in bronchoalveolar lavage fluid were quantified using Enzyme-Linked Immunosorbent Assay (ELISA). The main components of GDQ were identified through Ultra-High-Performance Liquid Chromatography-High-Resolution Mass Spectrometry (UHPLC-HRMS). Additionally, a combination of serum metabolomics and 16S gene sequencing of lung microbiota was employed to pinpoint key targets mediating the therapeutic effects of GDQ in the treatment of PM2.5-induced lung injury.ResultsThe findings indicated that GDQ had the capability to reduce the pathological changes of lung tissue and mitigate inflammatory exudation in the lungs. 16S rRNA gene sequencing revealed that GDQ effectively reduced the richness and diversity of the pulmonary microbiome induced by PM2.5 and restored the overall structure of the pulmonary microbiome. Metabolomic analysis identified 65 potential differential metabolites that may contribute to GDQ’s attenuation of PM2.5-induced lung injury. These metabolites were mainly enriched in the Phospholipase D signaling pathway, Metabolism of xenobiotics by cytochrome P450, and Glutathione metabolism.ConclusionOur research offers valuable insights into how GDQ operates to mitigate PM2.5-induced lung injury through the modulation of lung microbiota and serum metabolome. These findings may have important implications for the development of effective strategies to protect against lung injury caused by PM2.5.